K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

AH
Akai Haruma
Giáo viên
28 tháng 7 2019

a)

\(x^4+4=(x^2)^2+2^2+2.x^2.2-4x^2\)

\(=(x^2+2)^2-(2x)^2=(x^2+2-2x)(x^2+2+2x)\)

b)

\(64x^4+81=(8x^2)^2+9^2+2.8x^2.9-144x^2\)

\(=(8x^2+9)^2-(12x)^2=(8x^2+9-12x)(8x^2+9+12x)\)

c)

\(x^8+4=(x^4)^2+2^2+2.x^4.2-4x^4\)

\(=(x^4+2)^2-(2x^2)^2=(x^4+2-2x^2)(x^4+2+2x^2)\)

AH
Akai Haruma
Giáo viên
28 tháng 7 2019

d)

\(x^4+18x^2=(x^2)^2+18^2+2.x^2.18-36x^2\)

\(=(x^2+18)^2-(6x)^2=(x^2+18-6x)(x^2+18+6x)\)

e)

\(x^4+3x^2+4=(x^2)^2+2^2+2.x^2.2-x^2\)

\(=(x^2+2)^2-x^2=(x^2+2-x)(x^2+2+x)\)

f)

\(x^4-7x^2+1=(x^4-2x^2+1)-9x^2\)

\(=(x^2-1)^2-(3x)^2=(x^2-1-3x)(x^2-1+3x)\)

29 tháng 6 2019

a) \(x^2+12x+35\)

\(=x^2+5x+7x+35\)

\(=\left(x^2+5x\right)+\left(7x+35\right)\)

\(=x\left(x+5\right)+7\left(x+5\right)\)

\(=\left(x+5\right)\left(x+7\right)\)

b)\(x^2-x-56\)

\(=x^2+7x-8x-56\)

\(=\left(x^2+7x\right)-\left(8x+56\right)\)

\(=x\left(x+7\right)-8\left(x+7\right)\)

\(=\left(x+7\right)\left(x-8\right)\)

c)\(5x^2-x-4\)

\(=5x^2-5x+4x-4\)

\(=\left(5x^2-5x\right)+\left(4x-4\right)\)

\(=5x\left(x-1\right)+4\left(x-1\right)\)

\(=\left(x-1\right)\left(5x+4\right)\)

29 tháng 6 2019

TL:

a)\(x^2+5x+7x+35\) 

 =\(x\left(x+5\right)+7\left(x+5\right)\) 

=\(\left(x+7\right)\left(x+5\right)\) 

b) \(x^2-x-56\)

  =\(x^2+7x-8x-56\) 

=\(x\left(x+7\right)-8\left(x+7\right)\) 

=\(\left(x-8\right)\left(x+7\right)\) 

d)\(4x^4+1=\left(2x^2\right)^2+4x^2+1-4x^2\) 

=\(\left(2x^2+1\right)^2-4x^2\) 

=\(\left(2x^2+1+4x\right)\left(2x^2+1-4x\right)\)

.......................(tự lm)

hc tốt

26 tháng 12 2018

tự làm

15 tháng 7 2016

a)x^2-(a+b)x+ab

= x^2 - ax - bx + ab

= (x^2 - ax) - (bx - ab)

= x(x-a) - b(x-a)

= (x-b)(x-a) 

b)7x^3-3xyz-21x^2+9z

c)4x+4y-x^2(x+y)

= 4(x + y) - x^2(x+y)

= (4-x^2) (x+y)

= (2-x)(2+x)(x+y)

d) y^2+y-x^2+x

= (y^2 - x^2) + (x+y)

= (y-x)(y+x)+ (x+y)

= (y-x+1) (x+y)

e)4x^2-2x-y^2-y

= [(2x)^2 - y^2] - (2x +y)

= (2x-y)(2x+y) - (2x+y)

= (2x -y -1)(2x+y)

f)9x^2-25y^2-6x+10y

31 tháng 8 2021

ko biết làm

 

29 tháng 9 2016

a, x^2 + 5x +4

= x^2 + 1x + 4x + 4

= (x^2 + 1x) + (4x + 4)

= x ( x + 1 ) + 4 ( x + 1 )

= (x + 1) (x + 4)

b, x^2 - 6x + 5

= x^2 - 1x - 5x + 5

= (x^2 - 1x) - (5x - 5)

= x (x - 1) - 5 (x - 1)

= (x - 1) (x - 5)

c, x^2 + 7x + 12

= x^2 + 3x + 4x + 12 

= (x^2 + 3x) + (4x + 12)

= x (x + 3) + 4 (x + 3)

= (x + 3) (x + 4)

d, 2x^2 - 5x + 3

= 2^x2 - 2x - 3x + 3

= 2x (x - 1) - 3 (x - 1)

= (x-1) (2x - 3)

e, 7x  - 3x^2 - 4

= 3x + 4x - 3x^2 - 4

= (3x - 3x^2) + (4x - 4)

= 3x (1 - x) + 4 (x - 1)

= 3x (1-x) - 4 (1 - x)

= (1 - x) (3x - 4)

f, x^2 - 10x + 16

= x^2 - 2x - 8x + 16

= (x^2 - 2x) - (8x - 16)

= x (x - 2) - 8 (x - 2)

= (x - 2) (x - 8)

29 tháng 9 2016

a, (x+1)(x+4)

b,(x-5)(x-1)

c,(x+3)(x+4)

d,(2x-3)(x-1)

e,(-3x+4)(x-1)

f, (x-8)(x-2)

16 tháng 6 2017

a)\(3x^2-8x+4\)

\(=3x^2-2x-6x+4\)

\(=x\left(3x-2\right)-2\left(3x-2\right)\)

\(=\left(x-2\right)\left(3x-2\right)\)

b)\(4x^4+81\)

\(=4x^4+36x^2+81-36x^2\)

\(=\left(2x^2+9\right)^2-36x^2\)

\(=\left(2x^2-6x+9\right)\left(2x^2+6x+9\right)\)

c)\(x^8+98x^4+1\)

\(=\left(x^8+2x^4+1\right)+96x^4\)

\(=\left(x^4+1\right)^2+16x^2\left(x^4+1\right)+64x^4-16x^2\left(x^4+1\right)+32x^4\)

\(=\left(x^4+8x^2+1\right)^2-16x^2\left(x^4-2x^2+1\right)\)

\(=\left(x^4+8x^2+1\right)^2-16x^2\left(x^4-2x^2+1\right)\)

\(=\left(x^4+8x^2+1\right)^2-\left(4x^3-4x\right)^2\)

\(=\left(x^4+4x^3+8x^2-4x+1\right)\left(x^4-4x^3+8x^2+4x+1\right)\)

d)\(x^4+6x^3+7x^2-6x+1\)

\(=x^4+3x^3-x^2+3x^3+9x^2-3x-x^2-3x+1\)

\(=x^2\left(x^2+3x-1\right)+3x\left(x^2+3x-1\right)-\left(x^2+3x-1\right)\)

\(=\left(x^2+3x-1\right)\left(x^2+3x-1\right)\)\(=\left(x^2+3x-1\right)^2\)

2 tháng 9 2018

\(x^3-4x^2-8x+8\)

\(=x^3+2x^2-6x^2-12x+4x+8\)

\(=x^2\left(x+2\right)-6x\left(x+2\right)+4\left(x+2\right)\)

\(=\left(x+2\right)\left(x^2-6x+4\right)\)